1998
DOI: 10.1111/j.1439-0523.1998.tb01947.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of QTL for southwestern corn borer resistance, plant height and flowering in tropical maize

Abstract: Development of multiple insect resistance in tropical maize represents a major effort of the maize breeding programme at CIMMYT. Resistance to the southwestern corn borer (SWCB) is polygenically controlled with primarily additive gene action. Our main objective was to identify quantitative trait loci (QTL) involved in resistance to SWCB. Other objectives were to detect QTL in the same population for plant height, female flowering, and the anthesis-silking interval (ASI). A population of 472 F2 individuals deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
3
9

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 30 publications
6
60
3
9
Order By: Relevance
“…QTL located on chromosome 6 (6.04) which is also the location for other QTLs involved in diseases and pest resistance. For examples, two QTLs for Southwestern corn borer resistance (SWCB) on bin 6.04 [71], and on bin 6.06 [72], two QTLs for resistance to Fusarium moniliforme, an ear rot disease detected on bin 6.04 and 6.06 [73] or identified resistance genes, mdm1 for dwarf mosaic virus resistance (MDMV) [74], wsm1 resistance to wheat streak mosaic virus (WSMV) [75] and rhm1 conferring to resistance to Cochliobus heterostrophus, a fungul [76] etc. QTL for resistance to Aflatoxin (Aspergillus flavus) was detected on bin 9.01 [77].…”
Section: Discussionmentioning
confidence: 99%
“…QTL located on chromosome 6 (6.04) which is also the location for other QTLs involved in diseases and pest resistance. For examples, two QTLs for Southwestern corn borer resistance (SWCB) on bin 6.04 [71], and on bin 6.06 [72], two QTLs for resistance to Fusarium moniliforme, an ear rot disease detected on bin 6.04 and 6.06 [73] or identified resistance genes, mdm1 for dwarf mosaic virus resistance (MDMV) [74], wsm1 resistance to wheat streak mosaic virus (WSMV) [75] and rhm1 conferring to resistance to Cochliobus heterostrophus, a fungul [76] etc. QTL for resistance to Aflatoxin (Aspergillus flavus) was detected on bin 9.01 [77].…”
Section: Discussionmentioning
confidence: 99%
“…In quantitative trait loci analysis of related germ plasm, several unidentified traits related to southwestern corn borer resistance have been mapped near this region (Khairallah et al, 1998), but not to bin 6.02, where mir1 is found.…”
Section: Introductionmentioning
confidence: 99%
“…Fall armyworm larvae feed extensively on whorl leaf tissue, often resulting in crop losses. Genetic and quantitative trait loci analyses indicate that resistance to these Lepidoptera is a quantitative trait regulated by several genes (Williams et al, 1989;Khairallah et al, 1998). Traits such as high hemicellulose content, low protein content, and leaf toughness appear to be correlated with reduced larval growth (Williams et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Scott et al (1966) showed that resistance to the European corn borer, a lepidopteran pest just like C. partellus and B. fusca was conditioned by a relatively large number of genes with small effects on chromosomes 1, 2, 4, 6 and 8. The caution is that some QTL may not have been detected and, or, were dissimilar to those reported for related stem borers species due to the low heritability of the putative traits, and differences in trait characterization (Khairallah et al, 1998;Jiménez-Galindo et al, 2017). In a similar study, Samayoa et al (2015b) attributed such discrepancies to QTL by environment interaction effects and stressed the importance of making phenotypic evaluations in environments similar to those for which breeding materials are intended to be used.…”
Section: Quantitative Trait Loci For Resistance To Stem Borersmentioning
confidence: 90%